Blue upconversion enhancement by a factor of 200 in Tm 3+-doped tellurite glass by codoping with Nd 3+ ions - Rakov, N.; MacIel, G. S.; Sundheimer, M. L.; De, L.; Gomes, A. S. L.; Messaddeq, Younes [UNESP]; Cassanjes, F. C.; Poirier, G.; Ribeiro, Sidney José Lima [UNESP] (AIP Publishing, 2002)
We investigated near-infrared-to-blue upconversion from thulium (Tm 3+) doped in tellurite glasses upon continuous wave excitation near 800 nm. We observed an enhancement of over two orders of magnitude of the upconverted emission at ∼480nm when neodymium (Nd 3+) ions were codoped with Tm 3+ ions. For comparison, using a Tm 3+:Nd 3+ codoped fluorozirconate glass as a reference material we observed a 40-fold enhancement of the blue emission. Analysis of the blue emission for samples with different doping levels of Nd 3+ ions showed that energy transfer between Nd 3+ and Tm 3+ is the mechanism responsible for the enhancement in upconversion. © 2002 American Institute of Physics. © 2002 American Institute of Physics.
Keywords: Blue emission; Blue upconversion; Co-doped; Co-doping; Continuous Wave; Doping levels; Fluorozirconate glass; Orders of magnitude; Reference material; Tellurite glass; Up-conversion; Doping (additives); Energy transfer; Glass; Ions; Tellurium compounds; Thulium; Neodymium